2021
DOI: 10.1093/jpp/rgab075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,3-dimethyl-6-oxopyrano[3,4-c]pyridines and their antiplatelet and vasodilatory activity

Abstract: Objectives Both pyridine and pyrano derivatives have been previously shown to possess biologically relevant activity. In this study, we report the incorporation of these two scaffolds into one molecule. Methods The designed 3,3-dimethyl-6-oxopyrano[3,4-c]pyridines were synthesized by the acylation of enamine under Stork conditions followed by condensation of formed β-diketones with 2-cyanoacetamide. The structures of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…These experiments were analogous to our previous experiments with lysis of erythrocytes [ 19 ]. Human erythrocyte suspension was obtained by firstly centrifuging whole blood at 2700× g for 10 min and discarding the supernatant.…”
Section: Methodssupporting
confidence: 76%
“…These experiments were analogous to our previous experiments with lysis of erythrocytes [ 19 ]. Human erythrocyte suspension was obtained by firstly centrifuging whole blood at 2700× g for 10 min and discarding the supernatant.…”
Section: Methodssupporting
confidence: 76%
“…We synthesized terminal alkines from the 3(6)-hydroxy derivatives of cyclopenta[ c ]pyridine 1a [ 25 ], 5,6,7,8-tetrahydroisoquinolines 1b – d [ 25 ], pyrano [3,4- c ]pyridines 1e – g [ 14 , 26 ], and 2,7-naphtyridines 1h , i [ 27 ] to obtain the aimed hybrids, the 1,2,3-triazoles. It should be mentioned that tautomerism is possible in compound 1 lactam-lactim (NH/OH) via proton-migration of a hydrogen atom between the two basic centers.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work we demonstrated that the terminal triple bond was obtained based on the 3(6)-hydroxy derivatives of bicyclic pyridines 1 , and the compound was found to have strong antiplatelet and vasodilatory potential, as well as an IC 50 twice as low as that of the clinically used acetylsalicylic acid [ 14 ]. The azido group was synthesized based on the 6-piperazino derivatives of pyrano [3,4- c ]pyridines, which show pronounced neurotropic [ 15 , 16 ] and antimicrobial [ 17 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…The most potent compound, papaverine, had an IC 50 of 26.9 ± 12.2 μM followed by bulbocapnine with an IC 50 of 30.7 ± 5.4 μM. The IC 50 of the clinical standard ASA was 23.8 ± 10.4 μM [ 19 ]. Other alkaloids were clearly less active with IC 50 values > 50 μM.…”
Section: Resultsmentioning
confidence: 99%
“…An initial screening of the antiplatelet effects was performed with whole human blood using an impedance aggregometer Multiplate ® (Roche, Switzerland) [ 34 ]. The detailed measurement procedure has been previously described [ 19 ]. In brief, 300 μL of whole blood was diluted with an equivalent amount of preheated 0.9% sodium chloride and incubated for 3 min at 37 °C with 5 μL of the appropriate tested compound (dissolved in DMSO, final concentration < 1%) or DMSO (blank sample).…”
Section: Methodsmentioning
confidence: 99%